Climate proxy data from SG-1 drill core (2.69-0.08 Ma; Qaidam Basin, NE Tibetan Plateau) - Erwin Appel; Christian Herb; Xiaomin Fang; Wenxia Han; Wolfgang Rösler; Jiuyi Wang; Yibo Yang (PANGAEA, 2019)
Knowing the evolution history of the climate systems in the Asian inland dominated by either the Westerlies or the Asian monsoon, and understanding their associated driving mechanisms are crucial for assessing future trends of climate and environmental conditions in this region, but both the evolution and mechanisms are still under debate. In this study, we present a comparative analysis of massive data from an accurately dated drill core retrieved from the Westerlies controlled western Qaidam Basin (QB), with records from the Chinese Loess Plateau (CLP) dominated by the East Asia summer monsoon (EASM), to track the time and frequency domain evolution patterns and dynamic changes of the QB and the CLP systems. The results infer two main conclusions. First, a critical transition in the evolution of Qaidam paleolake occurred at 0.8-0.6 Ma, characterized by striking changes in proxy variations and a system shift from periodic variations to more irregular fluctuations after 0.6 Ma. Second, a similar evolution pattern prevailed in the Qaidam paleolake region and in the EASM-dominated CLP between ~2.7 to ~1.2 Ma, but a divergence of both systems started at ~1.2 Ma and fully established after 0.6 Ma, when largely fluctuating climate conditions in the QB with a distinct drying trend was accompanied by synchronous largely fluctuated EASM with an increasing trend after 0.6 Ma. We suggest that ice sheet expansion in the Northern Hemisphere, promoted by co-occurrence of low obliquity amplitudes and low eccentricity, drove both systems across a threshold at ~1.2 Ma, and the internal forcing due to glaciation disturbed the previous response of both systems to solar insolation and led to the divergence of two systems. At ~0.9-0.8 Ma, a node of the 1.2-Myr obliquity cycle co-occurred with an eccentricity minimum, which together with coeval decrease in atmospheric CO2 concentration, could have facilitated a striking expansion of ice sheets. The resulting more equatorial and zonally oriented northern hemisphere westerly jet could serve as key factor leading to the final collapse of Qaidam paleolake after ~0.6 Ma, and the divergence of the QB and the CLP systems.